New Islamic Urbanism - Maneval, Stefan (UCL Press, 2019)
Since the dawn of the oil era, cities in Saudi Arabia have witnessed rapid growth and profound societal changes. As a response to foreign architectural solutions and the increasing popularity of Western lifestyles, a distinct style of architecture and urban planning has emerged. Characterised by an emphasis on privacy, expressed through high enclosures, gates, blinds, and tinted windows, 'New Islamic Urbanism' constitutes for some an important element of piety. For others, it enables alternative ways of life, indulgence in banned social practices, and the formation of both publics and counterpublics.